2013
DOI: 10.1371/journal.pone.0052316
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making under Risk of Loss in Children

Abstract: In human adults, judgment errors are known to often lead to irrational decision-making in risky contexts. While these errors can affect the accuracy of profit evaluation, they may have once enhanced survival in dangerous contexts following a “better be safe than sorry” rule of thumb. Such a rule can be critical for children, and it could develop early on. Here, we investigated the rationality of choices and the possible occurrence of judgment errors in children aged 3 to 9 years when exposed to a risky trade. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…They showed that 82% of respondents chose option B, the option with certainty for $2,400 over option A, which provided a 99% probability to gain either $2,400 or $2,500. This is a perfect example of how risk will affect judgment errors and rationality, leading individuals not to maximize profits and potential gains (Steelandt, Broihanne, Romain, Thierry, & Dufour, ). Additionally, Tversky and Kahneman () extended their findings to demonstrate how this certainty effect is sensitive to how the question is framed.…”
Section: Managing and Moderating Negative Impacts Of Relocation: The mentioning
confidence: 99%
“…They showed that 82% of respondents chose option B, the option with certainty for $2,400 over option A, which provided a 99% probability to gain either $2,400 or $2,500. This is a perfect example of how risk will affect judgment errors and rationality, leading individuals not to maximize profits and potential gains (Steelandt, Broihanne, Romain, Thierry, & Dufour, ). Additionally, Tversky and Kahneman () extended their findings to demonstrate how this certainty effect is sensitive to how the question is framed.…”
Section: Managing and Moderating Negative Impacts Of Relocation: The mentioning
confidence: 99%
“…Several groups have developed simplified decision making tasks with the aim of minimizing task difficulty for younger participants (Paulsen et al, 2011 , 2012 ; Weller et al, 2011 ). For example, in the first study to assess economic decision making in pre-school children, Steelandt et al ( 2013 ) assessed the rationality of choices and judgment errors made by 3- to 9-year-old children. Children were given an initial offering of a medium-sized piece of cookie and then choose either to keep that offer or risk it, by exchanging it for one of six cups that had more, less, or the same amount of cookie, chosen at random.…”
Section: Decision Making Under Riskmentioning
confidence: 99%
“…Steelandt et al ( 2013 ) found that 3- and 4-year-olds performed poorly while 5- and 6-year-olds were able to correctly distinguish profitable situations from non-profitable situations. The performance of the 3- to 4-year-olds may be due to economic decision-making not being present at this age, or the complexity of the paradigm.…”
Section: Decision Making Under Riskmentioning
confidence: 99%
“…In choosing between a certain option and a risky option of equal EV, children as young as age 5 are likely to select risky options more often than adults (Harbaugh, Krause, & Vesterlund, ). In a trading game providing a typical risky economic situation, Steelandt, Broihanne, Romain, Thierry, and Dufour () showed that children aged 5–9 years were risk‐seekers. It could be hypothesized that children simply do not comprehend probabilities.…”
Section: Introductionmentioning
confidence: 99%
“…In a trading game providing a typical risky economic situation, Steelandt, Broihanne, Romain, Thierry, and Dufour (2013) showed that children aged 5-9 years were risk-seekers. It could be hypothesized that children simply do not comprehend probabilities.…”
mentioning
confidence: 99%